Association of a Self-Paid Medically Supervised Weight Management Program with Reversal of Obesity-Associated Impaired Fasting Glucose - Vijaya Surampudi; Xinkai Zhou; Chi-Hong Tseng; David Heber; Zhaoping Li (Clinics and Practice, 2021)
Aims: The progression of prediabetes to T2DM can be delayed through diet modification and weight management. However, the intensive lifestyle program is often not covered by medical insurance. This retrospective analysis evaluates the association of a patient self-paid weight management program on an improvement of blood sugar in overweight and obese patients with impaired fasting glucose (IFG). Methods: The medical records of 4634 patients who participated in the self-pay UCLA Weight Management Program were reviewed and 2572 patients met the criteria for this retrospective analysis to examine whether this program was associated with the reversal of IFG over 3 months among 1396 patients with normal fasting glucose (NFG) and 1176 with IFG. Results: The patients with IFG lost comparable amounts of weight (10.5 ± 1.3 kg) at three months, as did the subjects with NFG (10.1 ± 1.3 kg). Fasting blood glucose in the IFG group decreased from 108.49 ± 6.4 to 101.8 ± 9.41 mg/dL (p < 0.0001) after three months. There were also significant reductions in triglycerides, and both systolic and diastolic blood pressure in both groups in association with weight loss. Conclusion: Our medically supervised self-pay multidisciplinary weight management program was associated with reduced fasting blood glucose levels in patients with IFG over three months with comparable weight loss to patients with NFG.